Peningkatan pengetahuan tentang hipertensi melalui program inovasi sehati pada pra lansia dan lansia di RW 6 Kelurahan Curug Cimanggis Depok - Farma, Ritta; Widya Shari, Weni (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Hypertension is one of the top 10 diseases in the Cimanggis Community Health Center working area with a total of 2,675 cases. There were 42 cases of hypertension that occurred in pre-elderly and elderly people in RW 6, Curug Village, Cimanggis. Based on the collected data, it is known that the level of knowledge of hypertension sufferers in RW 6, Curug Village is still low. The "INOVASI SEHATI" program is a counseling program regarding hypertension to pre-elderly and elderly people. The purpose of this activity is to increase the knowledge and awareness of pre-elderly and elderly people about hypertension using creative media. This study is an observational study with a quasi-experimental research design measured using a pre-test and post-test. The sampling technique used in this study was total sampling with a sample size of 42. The sample is a hypertension sufferer in the pre-elderly and elderly age groups. Data collection was carried out for one month in RW 6, Curug Village, Cimanggis, Depok using a quantitative method through the distribution of questionnaires. Based on the Wilcoxon Signed Rank Test calculation, the Z-value obtained was -542 with a p-value (Asymp. Sig. 2-tailed) of 0.000, which is less than the critical limit of 0.05. Therefore, Ha is accepted (a significant change in respondents' knowledge about hypertension occurred after receiving education). Twenty-nine of the 38 participants experienced an increase in their knowledge about hypertension. The results indicate that the "INOVASI SEHATI" health program successfully increased the knowledge and awareness of pre-elderly and elderly people about hypertension.